Motos para pista de lodo - Doeden, Matt. (Mankato, Minn. : Capstone Press, 2007)
Learn about dirt bikes, their design, and dirt bike racing.
Includes index.
Parallel Spanish and English texts.
Keywords: Trail bikes -- Juvenile literature; Trail bikes; Motorcycling